The André-Oort conjecture for Drinfeld modular varieties - Hubschmid, Patrik (Compositio mathematica, 2013)
We consider the analogue of the André-Oort conjecture for Drinfeld modular varieties which was formulated by Breuer. We prove this analogue for special points with separable reflex field over the base field by adapting methods which were used by Klingler and Yafaev to prove the André-Oort conjecture under the generalized Riemann hypothesis in the classical case. Our result extends results of Breuer showing the correctness of the analogue for special points lying in a curve and for special points having a certain behaviour at a fixed set of primes.
Gesehen am 05.01.2022